Rekonstruksi Ilmu Perpajakan Berbasis Paradigma Profetik Kuntowijoyo - Wahyu Aji Nugroho; Dian Suci Lestari; Samsuk Huda; Zuhrul Anam; Rahmini Hadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to reconstruct the science of taxation based on Kuntowijoyo's prophetic paradigm which consists of three main pillars: humanization, liberation, and transcendence. The research method used is qualitative with a conceptual analysis approach through literature study of Kuntowijoyo's thoughts and their relevance to contemporary taxation science. The results show that humanization in taxation is manifested through a tax system that places humans as subjects with dignity, not merely objects of revenue collection. Liberation is realized by freeing society from structural injustice in tax policies that tend to burden lower economic groups disproportionately. Transcendence provides an ethical-spiritual foundation that positions tax obligations not only as legal compliance but as moral responsibility towards social welfare based on transcendent values. The discussion reveals that the integration of the prophetic paradigm can transform positivistic-instrumentalist taxation science into a more humanist, just, and spiritually grounded discipline. This research concludes that prophetic-based taxation reconstruction offers an alternative framework for developing taxation science that is more relevant to the Indonesian context, where material and spiritual dimensions are integrated in achieving tax justice and sustainable economic welfare for all levels of society.